Perylene diimide copolymers with dithienothiophene and dithienopyrrole: Use in n‐channel and ambipolar field‐effect transistors. Issue 7 (5th January 2013) - Zhang, Shiming; Wen, Yugeng; Zhou, Weiyi; Guo, Yunlong; Ma, Lanchao; Zhao, Xingang; Zhao, Zhen; Barlow, Stephen; Marder, Seth R.; Liu, Yunqi; Zhan, Xiaowei
Abstract Solution‐processable polymers consisting of perylene diimide (PDI) acceptor moieties alternating with dithienothiophene (DTT), N‐dodecyl‐dithienopyrrole (DTP), or oligomers of these donor groups have been synthesized. We have, in addition to varying the donor, varied the N, N′ substituents of the PDIs. The thermal, optical, electrochemical, and charge‐transport properties of the polymers have been investigated. The polymers show broad absorption extending from 300 to 1000 nm with optical band gaps as low as 1.2 eV; the band gap decreases with increasing the conjugation length of donor block, or by replacement of DTT by DTP. The electron affinities of the polymers, estimated from electrochemical data, range from −3.87 to −4.01 eV and are slightly affected by the specific choice of donor moiety, while the estimated ionization potentials (−5.31 to −5.92 eV) are more sensitive to the choice of donor. Bottom‐gate top‐contact organic field‐effect transistors based on the polymers generally exhibit n‐channel behavior with electron mobilities as high as 1.7 × 10–2 cm2/V/s and on/off ratios as high as 106; one PDI‐DTP polymer is an ambipolar transport material with electron mobility of 4 × 10–4 cm2/V/s and hole mobility of 4 × 10–5 cm2/V/s in air. There is considerable variation in the charge transport properties of the polymers with the chemical structures. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013